Efektivitas Leaflet, Kipas Tangan, dan Ular Tangga terhadap Pengetahuan dan Sikap Ibu Tentang Balita Stunting - Alda Riau Gucci; Ratih Kurniasari; Eka Andriani (Lembaga Pengembangan Kinerja Dosen, 2025)
Introduction: Stunting in toddlers is one of the significant nutritional problems and is a global focus. The prevalence of stunting in West Java is 21.7%. In the prevalence of stunting per sub-district in Karawang Regency in 2020, Rengasdengklok (5.5%) was second after Ciampel. The purpose of this study was to see the effectiveness of the use of educational media on mothers' knowledge and attitudes regarding stunting. Method: This study used a quasi-experimental design with a pretest-posttest design. The statistical test used was the Paired Sample T-Test. Results: The results of the Paired Sample T-Test showed that leaflet media with a p-value of 0.005 (<0.05), hand fan media with a p-value of 0.008 (<0.05), and snakes and ladders game media with a p-value of 0.003 (<0.05) showed significant effectiveness in increasing mothers' knowledge of toddlers regarding stunting. The results of the Paired T-Test showed that leaflet media with a p-value of 0.002 (<0.05) and hand fan media with a p-value of 0.026 (<0.05) showed significant effectiveness on the attitudes of mothers of toddlers regarding stunting. Snakes and ladders game media with a p-value of 0.055 (>0.05) showed no change in the attitudes of mothers of toddlers regarding stunting. Conclusion: The study showed that leaflet media, hand fans, and snakes and ladders games showed significant effectiveness on mothers' knowledge. While leaflet and hand fan media showed effectiveness on mothers' attitudes, snakes and ladders media showed no change in mothers' attitudes.